Evaluation of home based postnatal care provided by accredited social health activist worker in a rural community of Haryana: a cross-sectional study - Grover, Kashish; Khanna, Pardeep; Chayal, Vinod; Verma, Ramesh; Kapoor, Roopam; Kumar, Tarun; Tiwana, Navraj; Kaushal, Pankaj (International Journal Of Community Medicine And Public Health, 2019)
Background: The post-natal period is the most critical time for the mother and the newborn. Most of the maternal deaths occur in first month of life. Based on these facts Government of India took an initiative, home based postnatal care (HBPNC), to follow up postnatal mothers and newborns for first six weeks. The present study assessed the quality of HBPNC provided by accredited social health activist (ASHA) workers and various factors associated with it. Methods: This cross-sectional study was conducted under Community Health Center, Dubaldhan in block Beri of Haryana. A total of 60 ASHA workers were visited and all the postnatal mothers under the supervision of each ASHA worker were included in the study. In this way 264 postnatal mothers were contacted. A scoring system was used to assess the quality of HBPNC given by ASHA worker. Results: Majority of ASHA workers were not able to record temperature and weight of the baby correctly. Regarding care of cord and danger signs in newborn only half (50%) of the mothers were counselled, whereas, only 48% mothers were counseled regarding care of eyes. Statistically significant association of quality of newborn care with education and training attended by ASHA workers was seen. Conclusions: Our study confirmed that most of the new born babies were not getting good quality of home based newborn care. Recent training attended by ASHA worker is highly associated with providing good quality newborn care to babies by ASHA workers.